2023
DOI: 10.1002/jex2.128
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age at birth influences protein and RNA content in human milk extracellular vesicles

Brett Vahkal,
Illimar Altosaar,
Eric Tremblay
et al.

Abstract: Human milk extracellular vesicles (HM EVs) are proposed to protect against disease development in infants. This protection could in part be facilitated by the bioactive EV cargo of proteins and RNA. Notably, mothers birth infants of different gestational ages with unique needs, wherein the EV cargo of HM may diverge. We collected HM from lactating mothers within two weeks of a term or preterm birth. Following purification of EVs, proteins and mRNA were extracted for proteomics and sequencing analyses, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that there is no significant difference in the proteins and mRNA contained in EVs in the breast milk of premature and full-term infants, but the immunomodulatory substances carried by EVs are significantly different. It is speculated that premature milk EVs are secreted by immune cells, while those of full-term infants of breast milk EVs are more likely to come from mammary epithelial cells [ 59 ]. However, it is widely believed that breast milk harbors a diverse and abundant microbial community originating from the surface skin, infant oral contamination, and the gut-breast axis, inferring that milk EVs could also contain a certain number of microbiota-derived EVs, which are involved in neonatal intestinal immune formation and colonization of gut microbiota, and serve as receptors for bioactive molecules in host cells [ 60 ].…”
Section: Evs In Health and Diseasementioning
confidence: 99%
“…Recent studies have shown that there is no significant difference in the proteins and mRNA contained in EVs in the breast milk of premature and full-term infants, but the immunomodulatory substances carried by EVs are significantly different. It is speculated that premature milk EVs are secreted by immune cells, while those of full-term infants of breast milk EVs are more likely to come from mammary epithelial cells [ 59 ]. However, it is widely believed that breast milk harbors a diverse and abundant microbial community originating from the surface skin, infant oral contamination, and the gut-breast axis, inferring that milk EVs could also contain a certain number of microbiota-derived EVs, which are involved in neonatal intestinal immune formation and colonization of gut microbiota, and serve as receptors for bioactive molecules in host cells [ 60 ].…”
Section: Evs In Health and Diseasementioning
confidence: 99%